The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.dnarep.2007.12.013
|View full text |Cite
|
Sign up to set email alerts
|

hRev7, putative subunit of hPolζ, plays a critical role in survival, induction of mutations, and progression through S-phase, of UV(254nm)-irradiated human fibroblasts

Abstract: Translesion synthesis (TLS) refers to mechanisms by which specialized DNA polymerases incorporate nucleotides opposite fork-blocking lesions and extend replication until standard replicative polymerases take over. The first eukaryotic TLS polymerase discovered, S. cerevisiae Polzeta, consists of catalytic subunit Rev3 and non-catalytic subunit Rev7. Human homologs of these two proteins have been identified. Studies by Lawrence, Maher, and colleagues comparing UV((254nm))-irradiated human fibroblast cell strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 22 publications
4
41
0
Order By: Relevance
“…21 The specificity of the Rev7 antibody used in this study was validated by various means as described previously. 28 The subcellular distribution of Rev7 was also confirmed in HCT116 cells and by using a previously-validated rabbit anti-Rev7 antibody 29 (data not shown).…”
Section: Subcellular Localization Of Rev7mentioning
confidence: 94%
See 1 more Smart Citation
“…21 The specificity of the Rev7 antibody used in this study was validated by various means as described previously. 28 The subcellular distribution of Rev7 was also confirmed in HCT116 cells and by using a previously-validated rabbit anti-Rev7 antibody 29 (data not shown).…”
Section: Subcellular Localization Of Rev7mentioning
confidence: 94%
“…Additionally, a previously-published siRNA sequence 5'-AGAA-GAAUCUUCAGUACUA-3' 46 was used to deplete RAN products (siRAN-4). For stable depletion, cells were transfected with a pSilencer vector either alone or expressing short hairpin against hRev7 (shRev7) 29 by using lipofectamine 2000 (Invitrogen) following the manufacturer's protocol. The cells were selected with 1 mg/ml puromycin and selected clones were tested for the depletion efficiency using Western blotting.…”
Section: Depletion Of Target Gene Productsmentioning
confidence: 99%
“…It has been reported that REV7 interacts with REV3 forming Pol , a DNA polymerase involved in translesion DNA synthesis, and suppression of REV7 impairs DNA damage tolerance in human fibroblasts (19,20,23). During embryogenesis, endogenous factors, such as metabolites, oxygen radicals, and nitrogen species, induce various types of DNA damage, and an effective DNA repair system is very important for normal development of organisms (46 -49).…”
Section: Discussionmentioning
confidence: 99%
“…REV7 also interacts with human REV1, but the biological significance of REV7 association with REV3 and REV1 in humans is unclear (20 -22). Human fibroblasts with siRNAmediated depletion of REV7 expression show high sensitivity to UV-induced cytotoxicity and reduced sensitivity to UV-induced mutagenesis compared with those in control lines, indicating that REV7 is required for tolerance to UV-induced DNA damage (23). Recently, it has been reported that Pol and REV1 are involved in homologous recombination repair of DNA double strand breaks, although its mechanism is not fully understood (24,25).…”
mentioning
confidence: 99%
“…24 Similar findings were also obtained in REV7-compromised chicken DT40 cells and human foreskin fibroblasts, indicating a conservative role of REV7 in TLS in eukaryotes. 25,26 REV7 is also called MAD2B because it shares high sequence homology with MAD2, a key regulator in mitotic checkpoint. 27 Although REV7 does not bind MAD1, an anchoring protein for MAD2 at the kinetochore at the onset of checkpoint activation, 28 REV7, like MAD2, is capable of binding CDH1 and/or CDC20, which are coactivators of anaphase-promoting complex (APC), to impede APC activation.…”
mentioning
confidence: 99%